Diversity and Abundance of Plankton in Mangrove Waters - Yonavin Maryon Titaley; Abdul Hamid A. Toha; Ricardo F. Tapilatu (Faculty of Agriculture Musamus University, 2021)
The mangrove forest is an environment that is very rich in nutrients and it becomes an important element for plankton growth. This article aims to determine the diversity and abundance of plankton species in the mangrove area. The method used in this writing is a literature study, by exploring written sources in the form of books, articles, journals, or other documents relevant to the problem being presented. The information obtained from the literature study can be used as a reference to strengthen the existing arguments. The results of the writing show that the abundance and diversity of plankton in mangrove waters are strongly influenced by the physical and chemical conditions of the water, local conditions, tides, zoning, and mangrove density. In general, phytoplankton from the Bacillariophyceae class dominate mangrove waters compared to zooplankton. A mangrove forest management strategy needs to be implemented so that it can function for organisms and the surrounding environment.